THE EFFECT OF THE OPERATING CYCLE, MARKET CONCENTRATION, OPERATING CASH FLOW AND INSTITUTIONAL OWNERSHIP ON THE PERSISTENCE OF PROFITS IN PT. INDOFOOD CBP SUKSES MAKMUR TBK - Dewi Fortuna; Thomas Sumarsan Goh; Elidawati; Edison Sagala (SEAN Institute, 2022)
The purpose of this study is to find out and analyze the extent of the effect of operating cycles, market concentration, operating cash flow and institutional ownership on profit persistence in PT. Indofood CBP Sukses Makmur Tbk. The data collection technique used is secondary data in the form of an annual report 2013-2020 from the company PT. Indofood CBP Sukses Makmur Tbk. Samples in this study were taken from the financial statements of PT. Indofood CBP Sukses Makmur Tbk Medan on a quarterly basis of 2013-2020 so that the data obtained is as much as 4 periods x 8 years = 32 data. The data to be analyzed by quantitative methods. The results showed that the Operating Cycle, Market Concentration, Operating Cash Flow and Institutional Ownership together have an effect and significantly on Profit Persistence in PT. Indofood CBP Sukses Makmur Tbk and only Operating Cash Flow have a positive effect on Profit Persistence in PT. Indofood CBP Sukses Makmur Tbk while other variables negatively affect the Persistence of Profit in PT. Indofood CBP Sukses Makmur Tbk.